2013
DOI: 10.1371/journal.pone.0056933
|View full text |Cite
|
Sign up to set email alerts
|

Sex Specific Differences in Fetal Middle Cerebral Artery and Umbilical Venous Doppler

Abstract: BackgroundThe incidence of several adverse pregnancy outcomes including fetal growth restriction are higher in pregnancies where the fetus is male, leading to suggestions that placental insufficiency is more common in these fetuses. Placental insufficiency associated with fetal growth restriction may be identified by multi-vessel Doppler assessment, but little evidence exists regarding sex specific differences in these Doppler indices or placental function. This study aims to investigate sex specific differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 24 publications
(26 reference statements)
7
25
1
Order By: Relevance
“…That analysis also establishes the directionality of the effect such that earlier fetal heart rate influences maternal heart rate. Variation in maternal physiological indicators, potentially as the result of fetal sex, may be less generally expected but aligned with the growing literature pointing to a differential role of fetal sex on the intrauterine milieu (Clifton, 2010; Ghidini & Salafia, 2005; Prior, Wild, Mullins, Bennett, & Kumar, 2013). Indeed, in the second century A.D., Soranus promoted the notion that women carrying male fetuses have better color as the result of the stimulation provided by the excessive movement of male fetuses and that pallor of women carrying female fetuses was the result of lack of such stimulation (Temkin 1991).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…That analysis also establishes the directionality of the effect such that earlier fetal heart rate influences maternal heart rate. Variation in maternal physiological indicators, potentially as the result of fetal sex, may be less generally expected but aligned with the growing literature pointing to a differential role of fetal sex on the intrauterine milieu (Clifton, 2010; Ghidini & Salafia, 2005; Prior, Wild, Mullins, Bennett, & Kumar, 2013). Indeed, in the second century A.D., Soranus promoted the notion that women carrying male fetuses have better color as the result of the stimulation provided by the excessive movement of male fetuses and that pallor of women carrying female fetuses was the result of lack of such stimulation (Temkin 1991).…”
Section: Discussionmentioning
confidence: 71%
“…These include the use of Doppler technology to measure blood flow in specific areas of the brain, including the middle cerebral artery, in response to maternal vocalizations (Emory, 2010; Feng, Raynor, Fiano, Graham, & Emory, 1997). Doppler flow studies have revealed a previously unknown sex difference in perfusion of the developing fetal brain (Prior et al, 2013). New tools available to map the connectivity of the developing human brain from the molecular to the functional were heretofore unimaginable (Kang et al, 2011; Thomason et al, 2013).…”
Section: Chapter 13 Fetal Neurobehavioral Research Reimaginedmentioning
confidence: 99%
“…Second, MCA Doppler evaluation itself is an unreliable method under circumstances like fetal head movement, engagement and compression of the fetal head during scan. Even significant sex-specific differences were reported in the MCA PI and MCA PSV [34] and gender-specific normal ranges should be arranged. Third, MCA measurement is an indirect estimation of blood flow in fetal cranium.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that ethnic differences in fetoplacental flow may be limited [42], but sex-specific differences in umbilical and cerebral blood flow may exist [43]. …”
Section: Methodsmentioning
confidence: 99%